Dreamland burning - Latham, Jennifer (Little, Brown and Co., 2017)
"When Rowan finds a skeleton on her family's property, investigating the brutal, century-old murder leads to painful discoveries about the past. Alternating chapters tell the story of William, another teen grappling with the racial firestorm leading up to the 1921 Tulsa race riot, providing some clues to the mystery"--Provided by publisher.